2021
DOI: 10.1155/2021/9358464
|View full text |Cite
|
Sign up to set email alerts
|

Anemia among Women Who Visit Bost Hospital for Delivery in Helmand Province, Afghanistan

Abstract: Background. Anemia is a global public health problem that affects a large number of pregnant women worldwide. In developed and developing countries, the number of pregnant women who become anemic ranges between 18% and 56%, respectively. The aim of this study was to determine the prevalence of anemia and factors associated with anemia among pregnant women who visit Bost Hospital for delivery in Helmand province, Afghanistan. Methods. This was a hospital-based cross-sectional study that included 787 pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…Hence financial constraints are challenging to access and afford nutritious foods [ 31 ]. Other socio-demographic factors like educational level and occupation were found as insignificant predictors of anemia in this study but were significant in other studies [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Hence financial constraints are challenging to access and afford nutritious foods [ 31 ]. Other socio-demographic factors like educational level and occupation were found as insignificant predictors of anemia in this study but were significant in other studies [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 75%
“…This is consistent with the findings of other studies, which found that women with low monthly income were significantly more susceptible to anemia than those with middle-income monthly income [1,19,21], indicating an inverse relationship between anemia prevalence and socioeconomic status. Other socio-demographic factors like educational level and occupation were found to be insignificant predictors of anemia in this study but were significant in other studies [25,26]. There was agreement with many studies that showed that increasing antenatal care (ANC) attendance during pregnancy is associated with a lower risk of pregnancy anemia [27,28].…”
Section: Discussionsupporting
confidence: 87%
“…Afghanistan Afghanistan, like Pakistan, is also considered a LMIC and has multiple research literature that updates on maternal and fetal health for its prevalence of anemia. During the years 2018-19, the prevalence of anemia among the total population of pregnant women in Afghanistan was 36.5%, according to WHO, which is considered a moderate health problem [40] . This prevalence is comparatively lower than that of Pakistan's, which happened to be 57% during the same time frame [40] .…”
Section: Comparing Pakistan With Other South Asian Countriesmentioning
confidence: 99%
“…During the years 2018-19, the prevalence of anemia among the total population of pregnant women in Afghanistan was 36.5%, according to WHO, which is considered a moderate health problem [40] . This prevalence is comparatively lower than that of Pakistan's, which happened to be 57% during the same time frame [40] . An observational study by Ahmadi et al in 2022 at Qarabagh District, Ghazani province, Afghanistan was conducted to evaluate the prevalence of anemia among 625 pregnant women receiving antenatal care.…”
Section: Comparing Pakistan With Other South Asian Countriesmentioning
confidence: 99%
See 1 more Smart Citation